No end in sight: the international drug control system once again baulks at the prospect of reform - Klein, Axel; Stothard, Blaine (Drugs and alcohol today, 2019)
PurposeIn two separate sections the authors summarise the observations, use the insights to reflect on some of the propositions made in the book, and follow the appeal of one of the authors to civil society and academics to “help governments out of the drug policy dilemma that is now facing them”. The paper aims to discuss this issue.Design/methodology/approachThe genre the authors follow here is ethnography and the material takes the form of reflective field notes. Since each author follows a particular set of interests the authors split the paper into two sections. There are no strong conclusions, safe that the concerns about the international drug control system were fully borne out by events on the floor.FindingsThe role of CSOs is critical in moving the process forward – but countries are likely to drift apart as the policy differences are becoming inrreconcilable.Research limitations/implicationsIt is imperative to develop new models of cooperation in the management of psychactive substances.Practical implicationsThis is in recognition that at national level just as much as at Commission on Narcotic Drugs (CND) and UN General Assembly Special Session the increased involvement of CSOs has been pivotal in shifting focus towards public health and human rights. This in turn has encouraged some nations to do the same in their domestic policies – and to stand up and say so in CND meetings.Social implicationsMore involvement of academics and editorial teams in the design of sustainable policies and practices.Originality/valueIn a critical report on the CND the authors challenge the viability of the international drug control regime in view of the emerging differences between different member states. This is the first attempt in the drug policy literature to assess the durability of the drug control regime as it is faced by the fast paced transformation of cannabis into a recognised medicine and regulated recreational substance. If the appearance of agreement is maintained this is entirely for diplomatic reasons and organisational benefit. In reality, the system is breaking apart and new methods for regulating drugs are emerging.